EVALUATION REPORT STUDY FIELD of CIVIL ENGINEERING at KAUNAS UNIVERSITY of TECHNOLOGY - Markou, George; Meidla, Tonu; Theodossiou, Nikolaos; Todorova, Marija Malenkovska; Gikys, Mindaugas; Bedulskij, Tomas (My University, 2022)
The evaluation of study fields is based on the Methodology of External Evaluation of Study Fields approved by the Director of the Centre for Quality Assessment in Higher Education (hereafter – SKVC) 31 December 2019 Order No. V-149. The evaluation is intended to help higher education institutions to constantly improve their study process and to inform the public about the quality of studies. The evaluation process consists of the main following stages: 1) self-evaluation and self-evaluation report prepared by Higher Education Institution (hereafter – HEI); 2) site visit of the expert panel to the higher education institution; 3) production of the external evaluation report (EER) by the expert panel and its publication; 4) follow-up activities.